2022
DOI: 10.24818/imc/2021/04.14
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Style, Interpersonal Relationships and the Quality of the Medical Act During the Covid-19 Pandemic Within a State Hospital

Abstract: Through this research approach, we aimed to identify the main characteristics of the leaders of the Colțea Clinical Hospital, in the conditions and context of the COVID-19 pandemic. We chose this approach in view of the fact that the pandemic was and still is a challenge for all medical staff in the medical unit, which could have led to changes in behaviors, interpersonal relationships, with potential influences on the medical act. The results indicate that within the medical unit there is a rather transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several studies have been conducted on healthcare services in Romania, some researchers looking at the performance of healthcare workers (Popa et al, 2022), while others have examined the impact of economic crises on the healthcare system (Carausu et al, 2017), and others focused on leadership style over quality of the medical act (Corbos et al, 2021). Additionally, researchers have also analyzed how the Romanian healthcare system responded to the COVID-19 pandemic (Dascalu, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted on healthcare services in Romania, some researchers looking at the performance of healthcare workers (Popa et al, 2022), while others have examined the impact of economic crises on the healthcare system (Carausu et al, 2017), and others focused on leadership style over quality of the medical act (Corbos et al, 2021). Additionally, researchers have also analyzed how the Romanian healthcare system responded to the COVID-19 pandemic (Dascalu, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Their findings confirmed that the implementation of such practices can foster organizational sustainability by promoting extensive enhancements in employees' psychological capital, job satisfaction, performance, and reducing burnout and turnover. In this regard, Corbos et al [46] correspondingly found that an efficient leadership style (i.e., transformational and transactional) would impose prolonged advantages on the workplace. This positively impacts the quality of employees' performance and their perception of interpersonal relationships in the workplace.…”
Section: Trust In Leaders and Job Performancementioning
confidence: 99%
“…Combining these leadership competencies with robust interpersonal abilities, adept communication, and a fervor for public health is imperative for leaders within the public health domain. Nurturing and honing these proficiencies among both existing and upcoming public health leaders can play a pivotal role in driving the progression of community health, diminishing health inequalities, and ultimately enhancing public health results(Corbos et al, 2021)…”
mentioning
confidence: 99%